Preparation and characterization of natural Hydroxyapatite from bovine bone - Shahrizal, M. H.; Sri Asliza, Md Amin; Mohd Nazree, Derman; Mohd Zaheruddin, Kasmuin (Universiti Sains Malaysia (USM), 2011)
International Conference on Young Chemist 2008 (ICYC 2008) organized by Universiti Sains Malaysia (USM), 18th - 20th June 2008 at Penang, Malaysia.